HISTORISITAS PENANGGALAN JAWA ISLAM - Fitrotun Nisa’, Izza Nur (UIN ALAUDDIN MAKASSAR, 2021)
The form of diversity in Indonesia is not only about ethnicity, race, religion, etc. It is also related to the calendar used by society in ancient times. The calendar or calendar in Indonesia to be precise on the island of Java is very diverse. Where each period uses a different calendar (from Pre-Islamic to Islam entered the island of Java). The diversity includes the use of the pre-national calendar, candrasengkala, Saka, Islam, Java Islam and AD. The writing of this paper was carried out by means of literature review (using a variety of literature, including books, journals, scientific articles, and so on). The result of his research is the Javanese Islamic calendar which is a form of acculturation of the Javanese calendar and the Islamic calendar. The beginnings of the Javanese Islamic calendar are 1555 J to 1626 J. The 1st Suro year of alip is on Friday Legi (A'ahgi = the year alip Jum'at legi). There are separate provisions in the Javanese Islamic calendar, namely the year following the Saka year and the calendar system using the hijriyah calendar system. In this day and age, the Javanese Islamic calendar system is inherent in the Javanese tradition of commemorating religious holidays, determining good and bad days of marriage, commemorating the yesterday's slametan procession, there are even communities that still hold tightly to the Javanese Islamic calendar or what is called the Aboge Islamic community.Keywords: calendar, Java, Islam.